EQA quantification HbA1c Diabetes– Long-term and SIGMA analytical performance for Twenty one Portuguese Laboratories - Miranda, Armandina (2017)
Glycated hemoglobin (HbA1c) plays a crucial role in the monitoring and diagnosis of diabetes. In Portugal 9,8% of the population has diabetes (HbA1c ≥ 6,5% or treatment with glucose-lowering medications). Six sigma metrics combine bias, precision, and allowable total error (Tea), and can be used for assessing the quality of the analytic phase. The main objective of this study was to apply a linear regression model for long-term evaluation of the precision and inaccuracy, and apply the sigma metric to evaluate the performance of laboratories in HbA1c quantification.